2023
DOI: 10.1021/acs.analchem.3c03219
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization-Free Photoelectrochemical Aptasensor for Atrazine Based on Bifunctional Graphene Signal Amplification and a Controllable Sulfhydryl-Assembled BiOBr/Ag NP Microinterface

Huanhuan Sun,
Ye Feng,
Ziwei Zhang
et al.

Abstract: Immobilization-free sensors (IFSs), with no requirement of fixing the recognition element to the electrode surface, have received increasing attention due to their unique advantages of reusable electrodes, not being limited by the load of the recognition element, and not being easily changed to the structure of the probe. In the present work, an effective visible light-driven immobilization-free photoelectric aptasensor for ultrasensitive detection of atrazine (ATZ) was proposed based on a reusable BiOBr/Ag NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The detection of atrazine at trace levels down to 5 × 10 −12 M is achieved by time-resolved fluorescence, while higher concentrations are detected by amperometry. By comparison, one of the most sensitive aptasensors developed so far has an LOD of 1.2 × 10 −12 M [ 231 ].…”
Section: Applications Of Extremozyme-based Biosensorsmentioning
confidence: 99%
“…The detection of atrazine at trace levels down to 5 × 10 −12 M is achieved by time-resolved fluorescence, while higher concentrations are detected by amperometry. By comparison, one of the most sensitive aptasensors developed so far has an LOD of 1.2 × 10 −12 M [ 231 ].…”
Section: Applications Of Extremozyme-based Biosensorsmentioning
confidence: 99%
“…Herbicides, attributed to their low price and high efficacy in weed control, , have been extensively used to improve the agricultural productivity in the world, but the abuse of herbicides incurs growing safety hazard to the environment and human health. For instance, atrazine (2-chloro-4-ethylamino-6-isopropylamino-strazine, ATZ), one of the most widely used triazine herbicide, is a selective pre-emergence or postemergence herbicide that is used to control broadleaf weeds and some gramineous weeds by inhibiting photocooperation in susceptible plants. , It has been considered to be a persistent pollutant in farmland soil, mature agricultural products, and groundwater due to its widespread application, long half-life, poor biodegradability, and apparent mobility . Studies have shown that ATZ is potentially toxic to the growth, development, reproduction, and immunity of organisms .…”
Section: Introductionmentioning
confidence: 99%
“…on the sensing electrode surface . However, the immobilization of biological elements usually makes it difficult to detect real samples in harsh conditions such as high ionic strength and high pH . At the same time, since PEC sensors require light illumination to excite the photoelectric signals, the high-energy optical radiation can also easily lead to the denaturation of the biorecognition elements, which affects their stability. , …”
Section: Introductionmentioning
confidence: 99%